Adherence to Adjuvant Hormonal Therapy and Associated Factors Among Women with Breast Cancer Attending the Tikur Anbessa Specialized Hospital, Addis Ababa Ethiopia, 2019: A Cross-sectional Study - Wako Z (Dove Medical Press, 2021)
Zerko Wako,1 Daniel Mengistu,2 Negalign Getahun Dinegde,2 Tseganesh Asefa,1 Mulugeta Wassie1 1Department of Medical Nursing, School of Nursing, College of Medicine and Health Science, University of Gondar, Gondar, Ethiopia; 2School of Nursing and Midwifery, College of Health Science, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Zerko Wako Tel +251918728268Email zerkowako1992@gmail.comBackground: In breast cancer patients, adherence to adjuvant hormone therapy (AHT) is uncertain. Seven in every 10 patients were hormone receptor positive and adjuvant hormone therapy (AHT) is prescribed for 5– 10 years for a woman with breast cancer. Therefore, the aim of this research was to examine adherence to adjuvant hormone therapy and related factors among women with breast cancer attending the Tikur Anbessa Specialized Hospital Oncology Center.Methods: An institutional-based cross-sectional study was conducted from March to April, 2019. Systematic random sampling technique was used to select participants. A semi-structured questionnaire was used. Medication possession ratio (MPR) was used where score ≥ 80% was adherence. Data were entered in EpiData version 4.4.2.1 and transferred to SPSS version 25, and analyzed using binary logistic regression.Results: Out of 216 women with breast cancer 209 participated in the study with a response rate of 97%. The overall adherence in this study was 77.5%. Getting social support (OR=3.959, 95%CI: 1.570– 9.980), being on anastrozole (OR=0.139, 95%CI: 0.040– 0.485), getting a thorough therapeutic communication about treatment (OR=4.590, 95%CI: 1.061– 19.863), undergoing mastectomy (OR=0.215, 95%CI: 0.059– 0.788), having side effects (OR=0.210, 95%CI: 0.085– 0.517) were found to be significantly associated with adherence to AHT.Conclusion: In general, the overall adherence to AHT was 77.5% for women with breast cancer. Factors such as types of adjuvant hormone therapy, lack of side effects, mastectomy, getting social support, and thorough therapeutic communication were strongly linked with adherence to them.Keywords: adherence, adjuvant hormone therapy, breast cancer, Ethiopia